Pemilihan Strategi Pemasaran Dengan Metode SWOT Dan TOPSIS - Abiddin, Moh Zainal; Utama, Dana Marsetiya; Mas’udin, Ilyas (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Marketing is an important activity of the company. The main purpose of company marketing is to increase profit. CV X is a trading company. The company’s problem is the stable product sales. Companies must determine the right marketing strategy. This study uses SWOT analysis to identify factors and formulate appropriate marketing strategies. The TOPSIS method is used to rank alternative marketing strategies. TOPSIS ranking show best and ideal strategy. Based on SWOT analysis are four marketing strategies alternative. the first priority marketing strategy is to expand the product marketing distribution network with a preference value of 0.497962. The second priority marketing strategy is to focus on one of the NPK variants with a preference value of 0.488088. The priority marketing strategy of three is to improve the quality service with a preference value of 0.465217. And four priority marketing strategy is the use of marketing strategy with the value of preference 0.462249.